Language development in kinder garden of Bancapata, Abancay - Huayhua Mamani, Hilda Maribel (2020)
This research sought to determine the main aspects of the language development of children in the Initial IIEE of Bancapata. The relevance of language development is an important issue, considering that the child's language is essential for communication. The non-probabilistic sample consisted of 40 children aged 3, 4 and 5 years from the initial educational institution of Bancapata. The methodology used was observation. They were applied a Form to know the associated factors and the Revised Navarra Oral Language Test PLON R (adaptation of Dioses, 2006). The main result found was that 53.6% of the children interviewed need to improve language development, followed by 14.3% of children, who are at a Delay level and 32.1% of children at the Normal level.